A new species of Carpenter Moths (Lepidoptera, Cossidae) from Tarbagatai (NE Kazakhstan) and Altai (SW Siberia, Russia) Mountains - Yakovlev, Roman V.; Shapoval, Nazar A.; Ivonin, Vadim V.; Knyazev, Svyatoslav A.; Kuftina, Galina N.; Masharskiy, Alexey E. (Zootaxa, 2020)
We described a new cossid species, Dyspessa ulgen sp. nov. from the Tarbagatai and Altai Mountains and compared it to other taxa of Dyspessa reported from the region (D. tristis, D. saldaitisi, D. saissanica), as well as to morphologically similar D. ulula. The new species is most closely related to D. ulula but differs from the latter in the characteristics of the male genitalia, wing pattern, and molecular data (a 658 bp fragment of the mitochondrial COI gene).